Fuzzy analytic hierarchy process for analysis of barriers to halal supply chain adoption in Indonesia - Utama, Dana Marsetiya; Bahtiar, Ardi Agustia (Institute of Advanced Engineering and Science, 2025)
The increasing awareness of the importance of halal certification has prompted companies to evaluate the barriers to adopting the halal supply chain. While this adoption has the potential for significant benefits, various barriers must be investigated. This study examines the barriers to adopting halal supply chains in small and medium-sized food enterprises (SMEs). The fuzzy analytical hierarchy process (fuzzy AHP) assesses and weighs the 30 identified barriers. The results showed that the main barriers to adopting a halal supply chain include understanding and awareness of the importance of halal certification, support from the government and related institutions, and companies' internal readiness to implement halal standards. In addition, other significant barriers were high certification costs, lack of funds to promote the halal industry, lack of willingness to adopt and implement halal in the supply chain, and lack of technology costs to manage supply chain processes by halal standards. The implications of this study suggest the need for better support strategies from the government and relevant agencies, as well as awareness and understanding-raising efforts among SMEs to overcome these barriers and facilitate the adoption of halal supply chains.